Effects of conjugated linoleic acid or betaine on the growth performance and fatty acid composition in backfat and belly fat of finishing pigs fed dried distillers grains with solubles - L.S. Wang; Z. Shi; R. Gao; B.C. Su; H. Wang; B.M. Shi; A.S. Shan (Animal, 2015)
The objectives of this study were to determine the effects of conjugated linoleic acid (CLA) or betaine on the growth performance, carcass characteristics and fatty acid composition in backfat and belly fat of pigs fed distillers dried grains with solubles (DDGS). Thirty-two (60±2 kg) crossbred barrows (Duroc×Landrace×Yorkshine) were assigned to one of four diets randomly: (1) the control diet containing no corn DDGS (control group); (2) the diet containing 30% corn DDGS (DDGS-fed group); (3) the diet containing 30% corn DDGS and 10 g/kg CLA (CLA-fed group); (4) the diet containing 30% corn DDGS and 1 g/kg BET (BET-fed group). The pigs fed DDGS showed that the percentages of C18:2, polyunsaturated fatty acid (PUFA) and iodine value (IV) increased, while C18:1, saturated fatty acid (SFA) and monounsaturated fatty acid (MUFA) decreased. Pigs fed the DDGS+CLA or DDGS+betaine diets showed the increased percentage of SFA, and the decreased percentage of C18:2, PUFA and IV. In conclusion, results confirmed that the diets containing 30% DDGS had no detrimental effects on growth performance, but increased the percentage of PUFA and IV and decreased the percentage of SFA and MUFA in the backfat and belly fat. However, supplementation with CLA or BET can part reverse these effects on carcass fat in finishing pigs.